Social and Physical Environment with Stunting Incidents in Toddlers - Yulianti Kristiani Banhae; Maria Agustina Making; Yohanes M. Abanit; Maria Sambriong (GLOBAL HEALTH SCIENCE GROUP, 2023)
Stunting is a global problem that is very trending and requires serious attention throughout the world. The problem of stunting is an intergenerational problem that requires recovery over a longer period of time compared to other forms of malnutrition. The aim of the research is to analyze the relationship between the social environment and sanitation with the incidence of stunting among toddlers in the Maubesi Community Health Center area, TTU Regency. Method: used was quantitative with a cross sectional research design. The total population is all mothers who have stunted toddlers at the Maubesi Community Health Center, 275 people. The sample for this study was 60 parents who had stunted toddlers. Data collection through questionnaires and KIA books. The research data was explained bivariately using the chi square test. The research results show that. The social environment that has a significant relationship with the incidence of stunting is parental education (p value = 0.000), and family income (p value = 0.021). The physical environment that has a significant relationship with the incidence of stunting is clean water sources (p value = 0.001)). The conclusion is that there is a significant relationship between the social and physical environment and the incidence of stunting in the Maubesi Health Center Working Area, North Central East Regency.